2018
DOI: 10.21079/11681/27365
|View full text |Cite
|
Sign up to set email alerts
|

Miter gate gap detection using principal component analysis

Abstract: The U.S. Army Corps of Engineers (USACE) operates and maintains 236 lock chambers at 191 lock sites on 41 waterways throughout the contiguous United States. Waterway navigational locks are important parts of the nation's infrastructure. Locks enable the flow of billions of dollars of commerce and support efforts for flood control. Proper maintenance of the locks and early detection of damage is crucial; however, due to shrinking budgets, adequate funding to apply traditional scheduled maintenance and visual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Currently we support small finite groups G in the SmallGrp library [91] of the computer algebra system GAP For classical groups, these data can in principle be generated automatically, but at present we implement by hand only a few representations we actually support.…”
Section: Group Theory Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Currently we support small finite groups G in the SmallGrp library [91] of the computer algebra system GAP For classical groups, these data can in principle be generated automatically, but at present we implement by hand only a few representations we actually support.…”
Section: Group Theory Datamentioning
confidence: 99%
“…Let us go through the example line by line:1. g=getGroup[8,3] sets the group D 8 to g. This line illustrates the ability of autoboot to obtain the group theory data from the SmallGrp library[91] of the computer algebra system GAP[92], which contains the necessary data of finite groups of order less than 2000 and many others.The pair (8, 3)is a way to specify a finite group in SmallGrp. It simply says that D 8 is the third group in their list of groups of order 8.…”
mentioning
confidence: 99%
“…The results of this study revealed that the 98% variance case is a better candidate for damage detection; therefore, the 92% variance case is not explored further in this paper. For the results of all damage and variance cases, refer to Eick et al [20] The two damage scenarios presented here will be a sudden-small and sudden-large gap, with simulated dimensions as listed in Table 5. To test the damage detection sensitivity, the changes in strain caused from the gap were superimposed on the measured data.…”
Section: Damage Detectionmentioning
confidence: 99%
“…The U.S. Army Corps of Engineers (USACE) operates and maintains 236 lock chambers at 191 lock sites on 41 waterways throughout the United States. Locks enable the flow of billions of dollars of commerce and support efforts for flood control [1]. Commercial barges lashed together as tows, with each barge capable of holding1400-1800 tons of cargo, utilize the U.S.'s extensive waterway network.…”
Section: Introductionmentioning
confidence: 99%
“…Proper maintenance of the locks and early detection of damage is crucial in maintaining the integrity and continuous operation of the waterways. However, due to shrinking budgets, adequate funding often not available to apply traditional scheduled maintenance and visual inspection [1]. To maintain the waterways at their current operational level and keep delays from growing beyond their current state a large investment is required [3].…”
Section: Introductionmentioning
confidence: 99%